THE CIVIL STATUS LEGALITY OF TRANSSEXUAL CITIZENS AND THE LEGAL CONSEQUENCES TO THEIR MARRIAGE - Mohammad Rayhan Ainal Ihram Warga Dalem, (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Transsexual refers to individuals who possess a tendency towards a personal and psychosocial identity similar to the opposite sex, prompting them to decide to live as a member of the opposite sex through sex reassignment surgery. The purpose of this study is to examine the legality of the data status of transsexual citizens and understand the legal consequences regarding their marriage from the perspective of civil law in Indonesia. The research method applied in this study is the normative juridical legal research method, utilizing the study of positive law relevant to the core of the research. The results show that a citizen applying for a change of sex status must include proof of deficiencies in psychological and psychiatric aspects based on scientific diagnosis, as well as proof of imperfections in the physical aspect through a series of tests according to the standards of the Indonesian Medical Association, so it is not simply because they have undergone sex change surgery. Looking at what is written in Articles 1 and 2 of Law No. 1 of 1974 on Marriage, it is understood that marriages conducted by transsexual citizens are not considered valid from the perspective of the state law, which reflects the provisions of each recognized religion in Indonesia, as no recognized religion in Indonesia allows the performance of sex reassignment surgery except for health reasons or sexual abnormalities.